2018
DOI: 10.1371/journal.pone.0195361
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of stunting and its associated factors among children 6-59 months of age in Libo-Kemekem district, Northwest Ethiopia; A community based cross sectional study

Abstract: BackgroundChildren in developing countries are highly vulnerable to impaired physical growth because of poor dietary intake, lack of appropriate care, and repeated infections. This study aimed at assessing the prevalence of stunting and associated factors among children 6–59 months of age in Libo-kemekem district, northwest Ethiopia.MethodsA community based cross sectional study was conducted in Libo-Kemekem from October 15 to December 15, 2015. The multistage sampling technique was employed to select 1,320 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
58
4
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 17 publications
13
58
4
13
Order By: Relevance
“…Pemberian ASI tidak Eksklusif, bahwa dengan pemberian ASI Eksklusif sangat erat dengan penurunan kejadian stunting pada anak. Oleh Karena itu anak yang tidak mendapatkan ASI secara eksklusif akan berisiko mengalami stunting 18 , dua analisis terbaru bahwa bayi yang disapih sebelum berusia 6 bulan akan lebih berisiko terkena stunting 19 pemberian ASI pada usia 0-5 bulan akan berkontribusi dalam menunurunkan kejadian stunting pada anak 18 , penelitian di Ethiopia anak yang diberikan ASI < 2 tahun berisiko 3,2 kali mengalami stunting 12 Penelitian di Indonesia Bayi yang tidak mendapatkan ASI berisiko stunting 20-22 23,24 , Penelitian di Mozambique bahwa durasi pemberian ASI berhubungan dengan stunting 25 .…”
Section: Diskusiunclassified
“…Pemberian ASI tidak Eksklusif, bahwa dengan pemberian ASI Eksklusif sangat erat dengan penurunan kejadian stunting pada anak. Oleh Karena itu anak yang tidak mendapatkan ASI secara eksklusif akan berisiko mengalami stunting 18 , dua analisis terbaru bahwa bayi yang disapih sebelum berusia 6 bulan akan lebih berisiko terkena stunting 19 pemberian ASI pada usia 0-5 bulan akan berkontribusi dalam menunurunkan kejadian stunting pada anak 18 , penelitian di Ethiopia anak yang diberikan ASI < 2 tahun berisiko 3,2 kali mengalami stunting 12 Penelitian di Indonesia Bayi yang tidak mendapatkan ASI berisiko stunting 20-22 23,24 , Penelitian di Mozambique bahwa durasi pemberian ASI berhubungan dengan stunting 25 .…”
Section: Diskusiunclassified
“…Stunting is a major public health problem in developed and developing countries [1,2]. Based on world health organization (WHO), stunting is de ned as gender-speci c height-for-age value of less than two standard deviations of the WHO Child Growth Standards [3].…”
Section: Introductionmentioning
confidence: 99%
“…The factors associated with stunting are very complex and interconnected with each other. The factors can be classified as distant factors, like socioeconomic status of the household, followed by intermediate factors, such as environmental factors and health service-related characteristics and immediate factors such as maternal, child and nutritional characteristics [6,[13][14][15][16][17]. A systematic review and meta-analysis of 21 studies in Africa found that the predictors of stunting were complementary feeding practice, maternal under nutrition, household food insecurity, economic growth, and maternal education, as principal determinants of stunting [6].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, different studies identified different risk factors associated with stunting [13][14][15][16]. A study in northern Ethiopia found that being female, belonging to age group of 25-59 months, and birth weight of <2.5 kg, mothers' lack of antenatal visits, and mistimed complementary feeding initiation were positively associated with childhood stunting; whereas educational status of the mother showed negative association [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation